The Utilization of the Monte Carlo Technique for Rational Drug Discovery - A. Toropova, Mariya; Raška, Ivan; A. Toropov, Andrey; Raskova, Mária (Combinatorial Chemistry & High Throughput Screening, 2016)
Quantitative structure – activity relationships (QSARs) are built up for three endpoints (i) blood-brain barrier permeability; (ii) butyrylcholinesterase (BChE) inhibitory activity; and (iii) for biological effect of antibacterial drugs. The models are based on utilization of the Monte Carlo technique. The CORAL software available on the Internet has been utilized for the calculations. The principles of validation of models together with principles of selection of potential therapeutic agents are suggested. An original version of the definition for the domain of applicability as well as the mechanistic interpretation of model calculated with the Monte Carlo technique are described. Advantages and disadvantages of the utilized approach are discussed.
Keywords: SMILES